Klasifikasi Emosi Tokoh Aku dalam Novel Kisah yang Pendek untuk Cinta yang Panjang Karya Puthut EA: Kajian Psikologi Sastra David Krech - Suryo Daru Santoso; Faraeza Afriani; Fiona Aulia Rosanti; Tegar Aldi Syah; Fikri Al Ihsan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This study aims to classify the emotions of the character "I" in the novel Short Story for Long Love by Puthut EA by using a literary psychology approach based on David Krech's theory of emotions. These emotions are grouped into four categories, namely basic emotions, sensory emotions, self-assessment emotions, and social relationship emotions. The research method used is qualitative descriptive with see-and-record techniques to identify various forms of emotions that appear in the text. The results of the study show that the character "I" experiences various emotions such as happiness, anxiety, fear, pride, doubt, disappointment, and regret. This variation of emotions describes the inner dynamics of the character in dealing with love, loss, self-struggle, and reflection on his life experiences. In addition, this analysis shows that the change in the character's mood is greatly influenced by the interaction with other characters and the situations they experience. This research enriches the study of literary psychology by providing a deeper understanding of the complexity of characters and their relevance in describing human emotional conditions in literary works.